ЧИННИКИ ЕФЕКТИВНОЇ ПРОФЕСІЙНОЇ РЕАЛІЗАЦІЇ СТУДЕНТІВ СОЦІОНОМІЧНИХ СПЕЦІАЛЬНОСТЕЙ - Грицюк, Ірина Михайлівна; Hrytsiuk, Iryna (Сімферополь ВД "АРІАЛ" Запорізький національний університет, 2013)
This article represents the factors of professional preparation of students that chose socionomy speciality. As swift development of Ukrainian society pulls out qualitatively new requirements not only to professional knowledge and abilities but also to personality qualities of future specialists.
Factors of effective professional realization of students of socionomy specialities.
Keywords: соціальні орієнтація; спрямованість; спеціаліст соціономічної сфери; соціальні якості; мотиваційна підструктура; інтереси; Social orientation; orientation; socionomy specialist; social qualities; motivational fine-tuning; interests